Design Review of Semarang-Bawen Toll Road - ADIB ASH SHIDDIQI (NIM 15004144), ALFA
The Semarang-Bawen arterial road, through Ungaran Regency is the connector of the northern region of Central Java to the southern region and DIY. Today, several segments of the roads are very crowded with its saturation degree (comparison between traffic volume and road capacity) over than 0.8. Therefore, to ensure undisturbed traffic movement, improvement of road capacity must be done. In this case, it is decided to build Semarang Bawen Toll Road. The hilly and steep slope of the field is one of the factors that must be considered in this Toll Road design. The route choice must consider several aspects and comprehensively studied to make sure it agrees with Toll Road Standard and also considering the budget efficiency. Good geometric designs have to guarantee the design speed value, the safety and comfort of road user. Vertical and horizontal alignments must fulfill standard requirements. Beside of geometric aspect, pavement design was also studied in this report. The pavement used in this case is rigid pavement using 24 cm concrete slab. In this report, design of surface drainage was also added with detailed design of side ditch and design choice analysis. Then, from the design, the volume of works is calculated to estimate construction cost. The different of route choice occured due to optimization of vertical alignments, as an impact, the number of curving roads and the degree of the curve is larger but the amount of soil works is less. In the rigid pavement design, the thickness of concrete slab is thinner. Designs of pavement refer to Manual of Cement Concrete Pavement Design 2003 issued by Department of Housing and Region Infrastructure. Apart from that, there are no significant differences in drainage design. The only difference is the side slope which is 1:1,5 compared to 1:2 because the Consultant take more attention on the practical construction works than theoretical aspect.